Ketepatan Sirkulasi Pengunjung di Area Kandang Burung pada Kebun Binatang Ragunan - Baihaqi, Achmad Achiyat; Avenzoar, Azkia (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
Ragunan Zoo is a zoo located in the Ragunan area, Pasar Minggu, South Jakarta, Indonesia. Established in 1864 as "Planten En Dierentuin" on a 2-hectare land donated by Raden Saleh. Significantly, visitors' interest in seeing animals increases, particularly birds. Birds are one of the favorite attractions for the public when visiting Ragunan Zoo. Ensuring a sufficient circulation area around the bird enclosures is crucial for the zoo management. To support the success of Ragunan Zoo as a popular tourist destination for the Indonesian public, pedestrian circulation is a vital factor to ensure its standard. The circulation, which has various classifications based on configuration, user, space relationships, and materials, makes it a complex issue that must be ensured for comfort. Research is conducted qualitatively and comparatively, by collecting data directly through site visits and comparing existing data.